Students’ Perspectives on the Teaching Profession and Their Interest in Enrolling in the Pre-Service Teacher Professional Education Program (PPG) - Emy Artuti; Abdul Rahman Azhari; Bejo Basuki; Ichyatul Afrom; Roso Sugiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
Understanding students' perspectives on the teaching profession and their interest in participating in the PPG program for prospective teachers is very important for improving teacher competence. Therefore, it is necessary to conduct a study on students' perspectives on the teaching profession and their interest in participating in the PPG program for prospective teachers. The objectives of this study are to determine: (1) students' perspectives on the teaching profession; (2) students' interest in participating in the PPG program; and (3) the influence of students' perspectives on the teaching profession on their interest in participating in the PPG program. The population in this study were students of the Faculty of Teacher Training and Education, University of Palangka Raya, class of 2022. The data collection technique used in this study was a survey method. The results of the study showed that students' perspectives on the teaching profession were in the moderate or sufficient category. This indicates that students' perspectives on the teaching profession are quite good and can foster their interest in participating in the PPG program for prospective teachers. Meanwhile, students' interest in participating in the PPG program for prospective teachers falls into the moderate or sufficient category. This indicates that students' interest in participating in the PPG program for prospective teachers is quite high. The results of the regression analysis show that there is an influence of students' perspectives on the teaching profession on their interest in participating in the PPG program for prospective teachers.-